God, Chance and Purpose Can God Have It BothWays? - Bartholomew, David J (Cambridge University Press, 2013)
this field. In a book of this kind a disclaimer is essential. Anyone attempting to span so many disciplines must, inevitably, echo St Paul,who asked, in a different context: ‘who is sufficient for these things?’ (2 Cor. 2.15) The short answer, of course, is: no one. But if the apologetic task is not to go by default someone must take the risk. My only claim is that I am a statistical scientist whose work has taken him into many other fields. As one of the most famous of my colleagues (the late John Tukey) once said, ‘the best thing about being a statistician is that you get to play in everyone else’s back yard’.